Composite material based on waste electroceramics as well as preparation method and application of composite material
By preparing composite materials based on waste electric porcelain and using raw materials such as waste electric porcelain and fly ash, the problems of solid waste recycling and mineral resource consumption are solved, high mechanical strength and fire resistance are achieved, supporting components suitable for high-temperature environments are reduced Environmental pollution and resource consumption.
Patent Information
- Application Number
- CN202311528446.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-11-14
AI Technical Summary
The prior art does not involve the use of waste electric porcelain and fly ash to prepare composite materials based on waste electric porcelain, resulting in the problem of solid waste recycling and mineral resource consumption not being effectively solved.
Waste porcelain, fly ash, potassium source and alumina are used as the main raw materials, and composite materials are prepared by mixing, stirring, pressing, drying and sintering processes, preferably particle size combination and binder use to improve material performance.
It realizes high mechanical strength composite materials, which can be used in high temperature and high strength environments, reduce environmental pollution, save resource consumption, and improve economic value.
Smart Images

Figure BDA0004552945580000081 
Figure BDA0004552945580000082 
Figure HDA0004552945860000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of inorganic materials, and in particular relates to a composite material based on waste electric porcelain, and specifically, relates to a composite material based on waste electric porcelain, and a preparation method and application thereof. Background Art
[0002] Refractory materials generally refer to inorganic non-metallic materials with a refractoriness above 1580℃. It includes natural ores and various products made through certain processes according to certain purpose requirements. It has certain high-temperature mechanical properties and good volume stability, and is a necessary material for various high-temperature equipment. It is one of the important development processes of my country's industry, mainly used in the steel industry, building materials industry, non-ferrous metal industry, chemical industry, etc. They are important pillars supporting the rapid development of my country's economy. However, since refractory raw materials are consumables and due to the intensification of national trade, the exhaustion of refractory raw materials must be considered.
[0003] At the same time, the ceramic industry is developing rapidly. Among them, insulators are a type of ceramics used in power systems as supporting and insulating components. Due to the harsh working conditions, the preparation process of insulators requires more rigorous and precise preparation processes, so waste insulators have the advantages of heat resistance and high temperature resistance. Therefore, how to make full use of waste insulators is the research direction of many technicians.
[0004] Chinese patent CN115710138A discloses a method for preparing high-temperature resistant lightweight thermal insulation material from waste electrical porcelain, which relates to the field of comprehensive utilization of solid waste and thermal insulation material. Waste electrical porcelain, bauxite and clay are used as raw materials, water is added to form slurry, hexadecyltrimethylammonium bromide (CTAB) is used as a foaming agent, a foam stabilizer is added, and the above mixed slurry is injected into a mold by a casting molding process, and then the mold is removed and dried, and the material is sintered at high temperature after drying to obtain the material.
[0005] Chinese patent CN115745585A discloses a method for preparing low-aluminum mullite refractory bricks using waste electrical porcelain. The method first uses waste electrical porcelain of different particle sizes as raw materials, water glass solution as a binder, aluminum ash and clay as wrapping materials, mixes the ingredients evenly in a certain proportion and naturally dries them at room temperature for 90 minutes; then weighs the materials and places them in a mold, and obtains a sample under the conditions of dry pressing at 15MPa and holding the pressure for 60s.
[0006] However, the prior art does not involve the use of waste electrical porcelain and fly ash to prepare a composite material based on waste electrical porcelain. Summary of the invention
[0007] In order to overcome the problems existing in the prior art, the present invention provides a composite material based on waste electrical porcelain and its preparation method and application. The present invention uses waste electrical porcelain as the main raw material to prepare the composite material based on waste electrical porcelain, which solves the problem of recycling solid waste on the one hand, and saves the consumption of mineral resources on the other hand; the present invention also uses fly ash as the main additive, which provides a new idea for the high-value utilization of coal-based solid waste in my country. The composite material based on waste electrical porcelain described in the present invention can be used under high temperature conditions due to its high mechanical strength (for example (high flexural strength)). In a high temperature and high-strength environment, it can bear supporting components, such as load-bearing and pressure-bearing components of kilns, etc. In general, it realizes the resource recycling and reuse of industrial solid waste and coal-based solid waste, reduces environmental pollution, and improves economic value under low-cost conditions to meet the needs of the industry.
[0008] One of the objects of the present invention is to provide a composite material based on waste electric porcelain, which contains waste electric porcelain, fly ash, a potassium source and alumina.
[0009] In a preferred embodiment, the potassium source is selected from potassium feldspar.
[0010] In a preferred embodiment, based on the waste electrical porcelain, fly ash, potassium source and alumina as 100wt%, the weight of the waste electrical porcelain is 45wt% to 80wt%, the weight of the fly ash is 5 to 40wt%, the weight of the potassium source is 2 to 20wt%, and the weight of the alumina is 0.5 to 15wt%.
[0011] For example, taking the waste electrical porcelain, fly ash, potassium source and alumina as 100wt%, the waste electrical porcelain accounts for 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt% or 80wt%, the fly ash accounts for 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt% or 40wt%, the potassium source accounts for 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt%, 16wt%, 18wt% or 20wt%, and the alumina accounts for 0.5wt%, 1wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt% or 15wt%.
[0012] In a further preferred embodiment, based on the waste electrical porcelain, fly ash, potassium source and alumina as 100wt%, the weight of the waste electrical porcelain is 60wt% to 70wt%, the weight of the fly ash is 15 to 25wt%, the weight of the potassium source is 5 to 15wt%, and the weight of the alumina is 1 to 10wt%.
[0013] In a preferred embodiment, the particle size of the waste electrical porcelain is less than 5 mm, preferably less than 1 mm.
[0014] In a further preferred embodiment, the waste electrical porcelain comprises a mixture of three particle sizes, and the three particle sizes are respectively less than 74 μm, 74 μm to 0.3 mm, and 0.3 to 0.6 mm.
[0015] Among them, the inventors found in experiments that the combination of the above three particle sizes has the best effect.
[0016] In a further preferred embodiment, the weight ratio of waste electrical porcelain smaller than 74 μm, waste electrical porcelain of 74 μm-0.3 mm, and waste electrical porcelain of 0.3-0.6 mm is (10-60):(10-20):(10-20), preferably (25-45):(12-18):(12-18).
[0017] For example, the weight ratio of waste electrical porcelain less than 74μm, waste electrical porcelain of 74μm-0.3mm, and waste electrical porcelain of 0.3-0.6mm is (10, 15, 20, 25, 30, 35, 40, 45, 50, 55 or 60):(10, 12, 14, 16, 18 or 20):(10, 12, 14, 16, 18 or 20).
[0018] In a preferred embodiment, the composite material based on waste electrical porcelain further contains a binder.
[0019] In a further preferred embodiment, the binder is selected from at least one of PVA and water glass, preferably PVA (polyvinyl alcohol).
[0020] In a further preferred embodiment, based on 100wt% of the waste electrical porcelain, fly ash, potassium source and alumina, the weight of the binder is 0.5-15wt%, preferably 1-10wt%, for example, 0.5wt%, 1wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt% or 15wt%.
[0021] The second object of the present invention is to provide a method for preparing a composite material based on waste electrical porcelain, which is preferably used to prepare the composite material based on waste electrical porcelain described in one of the objects of the present invention. The preparation method comprises: mixing raw materials including the waste electrical porcelain, the fly ash, the potassium source, the alumina and the optional binder, stirring evenly, pressing into shape, drying, and sintering to obtain the composite material based on waste electrical porcelain.
[0022] In a preferred embodiment, based on the total amount of the waste electrical porcelain, fly ash, potassium source and alumina as 100wt%, the amount of the waste electrical porcelain is 45wt% to 80wt%, the amount of the fly ash is 5 to 40wt%, the amount of the potassium source is 2 to 20wt%, and the amount of the alumina is 0.5 to 15wt%.
[0023] For example, based on the total amount of the waste electrical porcelain, fly ash, potassium source and alumina as 100wt%, the amount of the waste electrical porcelain is 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt% or 80wt%, the amount of the fly ash is 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt% or 40wt%, the amount of the potassium source is 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt%, 16wt%, 18wt% or 20wt%, and the amount of alumina is 0.5wt%, 1wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt% or 15wt%.
[0024] In a further preferred embodiment, based on the total amount of the waste electrical porcelain, fly ash, potassium source and alumina as 100wt%, the amount of the waste electrical porcelain is 60wt% to 70wt%, the amount of the fly ash is 15 to 25wt%, the amount of the potassium source is 5 to 15wt%, and the amount of the alumina is 1 to 10wt%.
[0025] In a preferred embodiment, based on the total amount of the waste electrical porcelain, fly ash, potassium source and alumina as 100wt%, the amount of the binder is 0.5-15wt%, preferably 1-10wt%, for example, 0.5wt%, 1wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt% or 15wt%.
[0026] In a preferred embodiment, the compression molding conditions include: a pressure of 2 to 18 MPa, and a pressure holding time of 20 to 200 seconds.
[0027] In a further preferred embodiment, the conditions for the compression molding include: a pressure of 5 to 15 MPa, and a holding pressure of 30 to 100 seconds.
[0028] For example, the conditions for the compression molding include: a pressure of 2 MPa, 4 MPa, 6 MPa, 8 MPa, 10 MPa, 12 MPa, 14 MPa, 16 MPa or 18 MPa, and holding the pressure for 20 seconds, 40 seconds, 60 seconds, 80 seconds, 100 seconds, 120 seconds, 140 seconds, 160 seconds, 180 seconds or 200 seconds.
[0029] The present invention does not require pressing under high pressure to obtain a material with excellent performance. Preferably, the pressing molding is a semi-dry pressing method.
[0030] In a preferred embodiment, the drying conditions include: a temperature of 50 to 150° C. and a time of 5 to 50 hours.
[0031] In a further preferred embodiment, the drying conditions include: a temperature of 80 to 130° C. and a time of 10 to 40 hours.
[0032] For example, the drying conditions include: a temperature of 50°C, 60°C, 80°C, 100°C, 120°C, 140°C or 150°C, and a time of 5h, 10h, 15h, 20h, 25h, 30h, 35h or 40h.
[0033] In a preferred embodiment, the sintering comprises: gradually raising the temperature from room temperature to T1 for sintering, T1=1300-1600°C; then gradually lowering the temperature from T1 to T2, T2=500-1000°C; and finally naturally cooling from T2.
[0034] For example, T1 = 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C or 1600°C; T2 = 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or 1000°C.
[0035] In a further preferred embodiment, the sintering comprises: gradually raising the temperature from room temperature to T1 for sintering, T1=1400-1600°C; then gradually lowering the temperature from T1 to T2, T2=600-1000°C; and finally naturally cooling from T2.
[0036] In a further preferred embodiment, the sintering comprises: gradually raising the temperature from room temperature to T1 for sintering, T1=1400-1500°C; then gradually lowering the temperature from T1 to T2, T2=700-900°C; and finally naturally cooling from T2.
[0037] In a preferred embodiment, multiple insulation steps are performed during the heating process of sintering, and the insulation time is 20 to 200 min, for example, 20 min, 40 min, 60 min, 80 min, 100 min, 120 min, 140 min, 160 min, 180 min or 200 min.
[0038] In a preferred embodiment, the sintering includes: the sintering system is heated to T0 at a heating rate of 1 to 10°C / min for sintering, T0 = 700 to 1200°C, and the temperature is kept for 3 to 7 times (preferably 4 to 6 times) during the heating process (preferably for 10 to 80 minutes); then the temperature is continued to be heated to T1 at a heating rate of 0.5 to 8°C / min, and the temperature is kept for 1 to 5 times (preferably 2 to 4 times) during the heating process (preferably for 20 to 150 minutes); the temperature is kept at T1 (preferably for 60 to 200 minutes), and then the temperature is reduced to T2 at a cooling rate of 1 to 10°C / min, and finally naturally cooled.
[0039] For example, the sintering includes: the sintering system is heated to T0 at a heating rate of 1°C / min, 2°C / min, 4°C / min, 6°C / min, 8°C / min or 10°C / min, T0 = 700°C, 800°C, 900°C, 1000°C, 1100°C or 1200°C, and the heating process is carried out for 3, 4, 5, 6 or 7 times (preferably 10min, 20min, 30min, 40min, 50min, 60min, 70min or 80min); and then the sintering is continued at a heating rate of 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 8°C / min or 10°C / min. T0 = 700°C, 800°C, 900°C, 1000°C, 1100°C or 1200°C. The temperature is raised to T1 at a heating rate of 1°C / min, 7°C / min or 8°C / min, and during the heating process, the temperature is kept warm for 1, 2, 3, 4 or 5 times (preferably for 20 min, 40 min, 60 min, 80 min, 100 min, 120 min, 140 min or 150 min); the temperature is kept warm at T1 (preferably for 60 min, 80 min, 100 min, 120 min, 140 min, 160 min, 180 min or 200 min), and then the temperature is reduced to T2 at a cooling rate of 1°C / min, 2°C / min, 4°C / min, 6°C / min, 8°C / min or 10°C / min, and finally cooled naturally.
[0040] In a further preferred embodiment, the sintering comprises: the sintering system is heated to T0 at a heating rate of 3 to 8 ° C / min for sintering, T0 = 800 to 950 ° C, and in the heating process, the temperature is respectively at 50 to 150 ° C (for example, 60 ° C, 80 ° C, 100 ° C, 120 ° C or 140 ° C), 250 to 350 ° C (for example, 260 ° C, 280 ° C, 300 ° C, 320 ° C or 340 ° C), 450 to 550 ° C (for example, 460 ° C, 480 ° C, 500 ° C, 520 ° C or 540 ° C), 650 to 750 ° C (for example, 660 ° C, 680 ° C, 7 00℃, 720℃ or 740℃), 850~900℃ (for example, 850℃, 860℃, 880℃ or 900℃) and keep warm for 20~60min; then continue to heat up to T1 at a heating rate of 1~5℃ / min, and keep warm at 980~1020℃ (for example, 980℃, 1000℃ or 1020℃), 1080~1120℃ (for example, 1080℃, 1100℃ or 1120℃), 1180~1220℃ (for example, 1180℃, 1200℃ or 1220℃) during the heating process, and the holding time is 40~120min. When the sintering temperature reaches T1, keep warm for 80~150min, then reduce to T2 at 3~8℃ / min, and finally cool naturally.
[0041] The endpoints and any values of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, the endpoint values of each scope, the endpoint values of each scope and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.
[0042] Compared with the prior art, the present invention has the following beneficial effects: (1) the composite material based on waste electrical porcelain of the present invention has beneficial flexural strength; (2) the surface of the composite material based on waste electrical porcelain of the present invention is glossy and has no obvious granularity; (3) the composite material based on waste electrical porcelain of the present invention is mainly composed of mullite in the physical phase and has fire resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Example 3 ( Figure 1 B) and Comparative Example 1 ( Figure 1 A) SEM image of the obtained sample.
[0044] Figure 2 The XRD patterns of Example 3 and Examples 5 to 6 are shown. DETAILED DESCRIPTION
[0045] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0046] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0047] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0048] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0049] According to the national standard GB / T 3810.3-2016, the boiling method and the Archimedes drainage method were used, and the open and closed porosity of the sample was measured by a density balance. According to the national standard GB / T 38978-2020, the three-point bending method was adopted, and a universal material testing machine was used to carry out a flexural test on all fired samples.
[0050] The raw materials include: waste electric porcelain with different particle sizes (0-74 μm, 74 μm-0.3 mm, 0.3 mm-0.6 mm, Shandong Laiwu Porcelain Insulator Co., Ltd., China), fly ash (average particle size 600 μm, Hebei Province, China), and feldspar (average particle size 600 μm, Shandong Province, China) as raw materials. Polyvinyl alcohol (PVA) (Aladdin, China) is used as a binder. The chemical composition of the main components of the waste electric porcelain (from Zibo Tengyun Economic and Trade Co., Ltd.) is shown in Table 1 and Table 2.
[0051] Table 1: Main components of waste electrical porcelain
[0052]
[0053] Table 2: Main components of fly ash
[0054]
[0055] [Example 1]
[0056] 1.665g of 0-74μm waste electric porcelain, 0.555g of 74μm-0.3mm waste electric porcelain, 0.555g of 0.3mm-0.6mm waste electric porcelain, 0.37g of fly ash, 0.37g of potassium feldspar, 0.185g of aluminum oxide and 0.185g of binder PVA are mixed uniformly to obtain a mixture, and then the obtained mixture is pressed into a cylindrical mold with a specification of Φ15×h 15mm and a rectangular block (45mm×6mm×6mm) by semi-dry pressing method in a mold with a pressure of 10MPa for 60 seconds, and then placed in a drying oven at 100℃ for 24 hours. The sintering system is sintered to 900℃ (T0) at 5° per minute, wherein the heat is kept at 100℃, 300℃, 500℃, 700℃, and 900℃ for 40min respectively. When the sintering temperature is higher than 900℃, sinter at 3° per minute to the final temperature of 1440℃ (T1), and keep at 1000℃, 1100℃, and 1200℃ for 60min. When the sintering temperature reaches 1440℃, keep it for 120min, then reduce it to 800℃ (T2) at 5° per minute, and finally cool naturally.
[0057] The flexural strength of the sample is 57MPa. It can be seen from the sample XRD that the main phase of the sample is mullite, indicating that the content of mullite phase is relatively high, proving that the sample has fire resistance. Since mullite has a high melting point, the obtained material has good high temperature resistance.
[0058] [Example 2]
[0059] The process of Example 1 was repeated, except that the raw materials were different: 1.295 g of 0-74 μm waste electric porcelain, 0.555 g of 74 μm-0.3 mm waste electric porcelain, 0.555 g of 0.3 mm-0.6 mm waste electric porcelain, 0.74 g of fly ash, 0.37 g of potassium feldspar, 0.185 g of aluminum oxide and 0.185 g of binder PVA. Other conditions remained unchanged.
[0060] The flexural strength of the sample is 77.3MPa. It can be seen from the sample XRD that the main phase of the sample is mullite, indicating that the content of mullite phase is relatively high, proving that the sample has fire resistance. Since mullite has a high melting point, the obtained material has good high temperature resistance.
[0061] [Example 3]
[0062] The process of Example 1 was repeated, except that the raw materials were different: 0.925 g of 0-74 μm waste electric porcelain, 0.555 g of 74 μm-0.3 mm waste electric porcelain, 0.555 g of 0.3 mm-0.6 mm waste electric porcelain, 1.11 g of fly ash, 0.37 g of potassium feldspar, 0.185 g of aluminum oxide and 0.185 g of binder PVA. Other conditions remained unchanged.
[0063] The flexural strength of the sample is 65.4MPa. It can be seen from the sample XRD that the main phase of the sample is mullite, indicating that the content of mullite phase is relatively high, proving that the sample has fire resistance. Since mullite has a high melting point, the obtained material has good high temperature resistance.
[0064] [Example 4]
[0065] The process of Example 1 was repeated, except that the raw materials were different: 0.555 g of 0-74 μm waste electric porcelain, 0.555 g of 74 μm-0.3 mm waste electric porcelain, 0.555 g of 0.3 mm-0.6 mm waste electric porcelain, 1.48 g of fly ash, 0.37 g of potassium feldspar, 0.185 g of aluminum oxide and 0.185 g of binder PVA. Other conditions remained unchanged.
[0066] The flexural strength of the sample is 73.6MPa. It can be seen from the sample XRD that the main phase of the sample is mullite, indicating that the content of mullite phase is relatively high, proving that the sample has fire resistance. Since mullite has a high melting point, the obtained material has good high temperature resistance.
[0067] [Example 5]
[0068] The process of Example 3 was repeated, except that the sintering process was different: the sintering system was sintered at 5° per minute to 900°C, wherein the temperature was kept at 100°C, 300°C, 500°C, 700°C, and 900°C for 40 minutes. When the sintering temperature was higher than 900°C (T0), it was sintered at 3° per minute to the final temperature T1 (1540°C), and kept at 1000°C, 1100°C, and 1200°C for 60 minutes. When the sintering temperature reached 1540°C, it was kept for 120 minutes, then reduced to 800°C (T2) at 5° per minute, and finally cooled naturally.
[0069] The flexural strength of the sample is 61.9MPa. It can be seen from the sample XRD that the main phase of the sample is mullite, indicating that the content of mullite phase is relatively high, proving that the sample has fire resistance. Since mullite has a high melting point, the obtained material has good high temperature resistance.
[0070] [Example 6]
[0071] The process of Example 3 was repeated, except that the sintering process was different: the sintering system was sintered to 900°C at 5°C per minute, and the temperature was kept at 100°C, 300°C, 500°C, 700°C, and 900°C for 40 minutes. When the sintering temperature was higher than 900°C (T0), it was sintered to the final temperature T1 (1340°C) at 3°C per minute, and kept at 1000°C, 1100°C, and 1200°C for 60 minutes. When the sintering temperature reached 1340°C, it was kept for 120 minutes, then reduced to 800°C (T2) at 5°C per minute, and finally cooled naturally.
[0072] The flexural strength of the sample is 52.1MPa. It can be seen from the sample XRD that the main phase of the sample is mullite, indicating that the content of mullite phase is relatively high, proving that the sample has fire resistance. Since mullite has a high melting point, the obtained material has good high temperature resistance.
[0073] [Example 7]
[0074] 1.093g of 0-74μm waste electric porcelain, 0.656g of 74μm-0.3mm waste electric porcelain, 0.656g of 0.3mm-0.6mm waste electric porcelain, 0.74g of fly ash, 0.37g of potassium feldspar, 0.185g of aluminum oxide and 0.185g of binder PVA. The obtained mixture is pressed into a cylindrical mold with a specification of Φ15×h 15mm and a rectangular block (45mm×6mm×6mm) by semi-dry pressing method in a mold with a pressure of 6MPa for 100 seconds, and then placed in a drying oven at 100℃ for 24 hours. The sintering system is sintered to 800℃ (T0) at 3° per minute, and the heat preservation is 60min at 80℃, 250℃, 450℃, 650℃ and 800℃ respectively. When the sintering temperature is higher than 800℃, sinter at 1℃ / min to the final temperature T1 (1400℃), and keep at 1000℃, 1100℃, and 1200℃ for 80min. When the sintering temperature reaches 1400℃, keep it for 150min, then reduce it to 700℃ (T2) at 3℃ / min, and finally cool it naturally.
[0075] The flexural strength of the sample is 50.49MPa. It can be seen from the sample XRD that the main phase of the sample is mullite, indicating that the content of mullite phase is relatively high, proving that the sample has fire resistance. Since mullite has a high melting point, the obtained material has good high temperature resistance.
[0076] [Example 8]
[0077] The process of Example 1 was repeated, except that the raw materials were different: 0.7568g of 0-74μm waste electric porcelain, 0.4541g of 74μm-0.3mm waste electric porcelain, 0.4541g of 0.3mm-0.6mm waste electric porcelain, 1.48g of fly ash, 0.37g of potassium feldspar, 0.185g of aluminum oxide and 0.185g of binder PVA. Other conditions remained unchanged. The obtained mixture was pressed into cylindrical molds with a specification of Φ15×h 15mm and rectangular briquettes (45mm×6mm×6mm) in a mold with a pressure of 18MPa for 30 seconds by semi-dry pressing, and then placed in a drying oven at 100°C for 24 hours. The sintering system was sintered to 950°C (T0) at 8°C per minute, wherein the heat was kept at 120°C, 350°C, 550°C, 750°C and 900°C for 30min respectively. When the sintering temperature is higher than 900℃, sinter at 5℃ / min to the final temperature T1 (1500℃), and keep at 1000℃, 1100℃, and 1200℃ for 40min. When the sintering temperature reaches 1500℃, keep it for 80min, then reduce it to 900℃ (T2) at 8℃ / min, and finally cool it naturally.
[0078] The flexural strength of the sample is 56.56MPa. It can be seen from the sample XRD that the main phase of the sample is mullite, indicating that the content of mullite phase is relatively high, proving that the sample has fire resistance. Since mullite has a high melting point, the obtained material has good high temperature resistance.
[0079] [Comparative Example 1]
[0080] The process of Example 1 was repeated, except that the sintering process was different: the sintering system was sintered at 5° per minute to 900°C, wherein the temperature was kept at 100°C, 300°C, 500°C, 700°C, and 900°C for 40 minutes respectively. When the sintering temperature was higher than 900°C, it was sintered at 3° per minute to the final temperature T1 (1140°C), and kept at 1000°C for 60 minutes. When the sintering temperature reached 1140°C, it was kept for 120 minutes, then reduced to 800°C (T2) at 5° per minute, and finally cooled naturally.
[0081] The flexural strength of the sample is 43.8MPa.
[0082] [Comparative Example 2]
[0083] The process of Example 3 was repeated, except that an equal amount of fly ash was used to replace the waste electrical porcelain. The results showed that:
[0084] The sample showed obvious overburning during the sintering process, with many pores on the surface and bulges around it. The sample's morphology could not be guaranteed and the flexural strength could not be measured.
[0085] [Test Example 1]
[0086] The samples obtained in Example 3, Example 6, Example 5 and Comparative Example 1 were analyzed (observed with the naked eye): the sizes of the sintered bodies of Comparative Example 1 and Example 6 were not significantly different from those of the green bodies, but the fired samples had obvious granularity; the fired sample of Example 3 had significantly lower granularity than that of Example 6 and Comparative Example 1, and had a certain gloss; and the sample of Example 5 had slight deformation after firing, but the glossiness did not change much.
[0087] [Test Example 2]
[0088] For Example 3 ( Figure 1 B) and Comparative Example 1 ( Figure 1 The sample obtained in A) was subjected to SEM detection, and the results were as follows Figure 1 shown.
[0089] Compared with Example 3: The surface of the sample in Example 1 is relatively rough. As the temperature increases, the surface smoothness of the sample increases and it transforms into ceramicization. The overall sample pore size gradually decreases. At the final temperature of 1140°C, the sample surface is relatively rough and has a larger unbonded surface.
[0090] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A composite material based on waste electrical porcelain, comprising waste electrical porcelain, fly ash, a potassium source and alumina.
2. The composite material based on waste electrical porcelain according to claim 1, characterized in that: The potassium source is selected from potassium feldspar; and / or, The particle size of the waste electrical porcelain is less than 5 mm, preferably less than 1 mm.
3. The composite material based on waste electrical porcelain according to claim 1, characterized in that: Taking the waste electrical porcelain, fly ash, potassium source and alumina as 100wt%, the weight of the waste electrical porcelain is 45wt% to 80wt%, the weight of the fly ash is 5 to 40wt%, the weight of the potassium source is 2 to 20wt%, and the weight of the alumina is 0.5 to 15wt%; preferably, the weight of the waste electrical porcelain is 60wt% to 70wt%, the weight of the fly ash is 15 to 25wt%, the weight of the potassium source is 5 to 15wt%, and the weight of the alumina is 1 to 10wt%.
4. The composite material based on waste electrical porcelain according to any one of claims 1 to 3, characterized in that: The composite material based on waste electrical porcelain further contains a binder; preferably, the binder is selected from at least one of PVA and water glass; more preferably, based on 100wt% of the waste electrical porcelain, fly ash, potassium source and alumina, the weight of the binder is 0.5-15wt%, preferably 1-10wt%.
5. A method for preparing a composite material based on waste electrical porcelain, preferably for preparing the composite material based on waste electrical porcelain according to any one of claims 1 to 4, the method comprising: The raw materials including the waste electrical porcelain, the fly ash, the potassium source, the alumina and the optional binder are mixed, stirred evenly, pressed into shape, dried and sintered to obtain the composite material based on the waste electrical porcelain.
6. The preparation method according to claim 5, characterized in that Based on the total amount of the waste electrical porcelain, fly ash, potassium source and alumina as 100wt%, the amount of the waste electrical porcelain is 45wt% to 80wt%, the amount of the fly ash is 5 to 40wt%, the amount of the potassium source is 2 to 20wt%, and the amount of the alumina is 0.5 to 15wt%; preferably, the amount of the waste electrical porcelain is 60wt% to 70wt%, the amount of the fly ash is 15 to 25wt%, the amount of the potassium source is 5 to 15wt%, and the amount of the alumina is 1 to 10wt%.
7. The preparation method according to claim 5, characterized in that Based on the total amount of the waste electrical porcelain, fly ash, potassium source and alumina being 100 wt %, the amount of the binder is 0.5 to 15 wt %, preferably 1 to 10 wt %.
8. The preparation method according to claim 5, characterized in that The conditions for the compression molding include: a pressure of 2 to 18 MPa, and a holding pressure of 20 to 200 seconds; preferably, a pressure of 5 to 15 MPa, and a holding pressure of 30 to 100 seconds; and / or, The drying conditions include: a temperature of 50 to 150° C. and a time of 5 to 50 hours; preferably, a temperature of 80 to 130° C. and a time of 10 to 40 hours.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The sintering includes: gradually heating from room temperature to T1 for sintering, then gradually cooling from T1 to T2, and finally naturally cooling from T2; wherein, T1 = 1300 ~ 1600 ° C, preferably, T1 = 1400 ~ 1600 ° C; T2 = 500 ~ 1000 ° C, preferably, T2 = 600 ~ 1000 ° C.
10. The preparation method according to claim 9, characterized in that The sintering process includes: heating the temperature to T0 at a heating rate of 1 to 10°C / min for sintering, where T0 = 700 to 1200°C, and keeping the temperature for 3 to 7 times (preferably 4 to 6 times) during the heating process (preferably for 10 to 80 minutes); then continuing to heat the temperature to T1 at a heating rate of 0.5 to 8°C / min, and keeping the temperature for 1 to 5 times (preferably 2 to 4 times) during the heating process (preferably for 20 to 150 minutes); keeping the temperature at T1 (preferably for 60 to 200 minutes), then cooling the temperature to T2 at a cooling rate of 1 to 10°C / min, and finally cooling naturally.
Citation Information
Patent Citations
Method for preparing high-temperature-resistant light heat insulation material from waste electroceramics
CN115710138A
A novel method of producing improved lightweight ceramic sand and uses thereof
CA3128590A1
Aluminum-silicon lightweight aggregate based on low-voltage electric porcelain waste material and preparation method thereof
CN103693944A
Sewage treatment biological filter material based on low-voltage electric porcelain waste and preparation method thereof
CN104058781A
Preparation method of porous ceramic with large mixing amount, low cost and high performance
CN107043274A
Cited By
Clay-added waste ceramic-based high-temperature-resistant material as well as preparation method and application thereof
CN121248267A
